2024
DOI: 10.1039/d4mh00116h
|View full text |Cite
|
Sign up to set email alerts
|

Microcage flame retardants with complete recyclability and durability via reversible interfacial locking engineering

Furong Zeng,
Lei He,
Jianwen Ma
et al.

Abstract: Flame retardants are effective in protecting materials from fire but pose environmental challenges due to limited recyclability. Urgently needed for the circular material economy are new flame retardants that are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…As the temperature increased, the carbon-to-oxygen ratio in PU/CCs increased, indicating an enhanced carbon sequestration capacity compared to neat PUs. In the FTIR spectra of neat PU, a reduction in the intensity of the carbonyl group (at 1710 cm −1 ) 51–54 was observed at 250 and 300 °C. Conversely, for PU/CCs, the characteristic absorption peak of the carbonyl group gradually disappeared at 250 °C, suggesting that the addition of CCs facilitated the cleavage of urethane bonds at lower temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…As the temperature increased, the carbon-to-oxygen ratio in PU/CCs increased, indicating an enhanced carbon sequestration capacity compared to neat PUs. In the FTIR spectra of neat PU, a reduction in the intensity of the carbonyl group (at 1710 cm −1 ) 51–54 was observed at 250 and 300 °C. Conversely, for PU/CCs, the characteristic absorption peak of the carbonyl group gradually disappeared at 250 °C, suggesting that the addition of CCs facilitated the cleavage of urethane bonds at lower temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In order to solve the environmental problems of traditional flame retardants, bio-based and recyclable phosphorus flame retardants have become the focus of research in recent years. Many “green” bio-based phosphorus flame retardants such as self-assembled ammonium polyphosphates (APP)/chitosan (CS)/carboxylated silicone oil (Si-COOH/Si), phytic acid (PA) and taurine (TA) compounds, PA@chitosan microsphere (CHTM) compounds, phosphorylation CS, arginine (AR)–phytic acid (PA) compounds, phosphorylated modified cellulose fibers, and bio-derived oligomeric polyphosphate . Compared to the unmodified natural materials such as chitosan and lignin, the phosphorus modified material either via chemical reaction or physical assembly exhibits much more excellent flame-retardant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Despite hierarchical RPUF composites having many merits as impact-resistant protective materials, their porous structures and organic components bring high flammability, which must be paid attention to. It is acknowledged that flame-retardant treatment on the surface of RPUF composites is one of the most effective methods to improve their fire resistance. , Polyelectrolyte composites are regarded as promising flame-retardant coatings due to their advantages, such as insolubility, excellent adsorption, good biocompatibility, convenient material extraction, low cost, and environmental friendliness. , Many attempts have been made to reduce the fire hazards of polymer composites. For example, Tao et al prepared a polyelectrolyte complex flame-retardant (PEC) by complexing cationic electrolyte chitosan (CS) with anionic electrolyte phytic acid (PA) and incorporated it into the ethylene-vinyl acetate copolymer (EVA) matrix to fabricate flame-retardant EVA composites . They found that the EVA composite containing 20 wt % PEC exhibited increased char residues at 600 °C and a lower peak of heat release rate (PHRR) value compared with that of neat EVA.…”
Section: Introductionmentioning
confidence: 99%